Nutritional Status of Reproductive Ethnic Woman Living in Chittagong Hill Tracts of Bangladesh: Influence of Socio-economic and Nutritional Factors - Sartaz Sadia; Kawser Mahbuba; Akhtaruzzaman Md.; Sheikh Nazrul Islam (International Journal of Nutrition, 2020)
Aim This cross-sectional study assessed the nutritional status of ethnic reproductive women aged between 15-40 years, comprising 85 lactating women (LW) and 86 non-pregnant-non-lactating women (NPNLW) who lived in various parts of three hilly districts (Bandarban, Khagrachari and Rangamati) of the Chittagong Hill Tracts (CHTs) of Bangladesh. Materials and Method Research tool was pretested semi-structured questionnaire for this observational study. Anthropometric indices like weight, height and mid-upper-arm-circumference (MUAC) were used in assessing the nutritional status. Results Most (44.4%) of the ethnic women were Marma, followed by Chakma (39.8%), Bam (8.2%) and Tripura (5.8%). No significant (P>0.05) differences were observed in socio-economic variables between LW and NPNLW. Overall, mean age of the women was 28 (±7.2) years; mean family income was 18,822.2 (±3091) BDT and majority (86%-87%) were reported to be food secured throughout the year. Mean Dietary calorie (2631±798 kcal) intake of both groups were up to the mark according to the recommended dietary allowances (RDAs) and most (80.3%-86%) of them also possessed good nutritional knowledge. However, no significant (P>0.05) differences were observed in dietary calorie intake and nutritional knowledge score between two groups of women. Overall, most (68.4%) of the women had normal body max index (BMI kg/m2), 11.7% were found to be undernourished or thin and 19.9% were overweight. It was noticed that better nutritional status of LW and NPNLW were significantly associated with literacy (P<0.05), occupancy in household chores (P<0.05), better income (P<0.05), food security (P<0.05), recommended calorie intake level (P<0.05) and better nutritional knowledge score (P<0.05). Conclusion This study showed that vast majority of the ethnic reproductive women of CHTs are in better nutritional status with normal BMI (kg/m2) and daily calorie intake according to RDA. Most of them were food secured and their nutritional knowledge score was also up to the mark. Better socio-economic condition, nutritional knowledge and accurate calorie intake play a vital role in achieving healthy nutritional status of the two women groups of CHTs.
Keywords: Nutritional Status